Case report: Reversible splenial lesion syndrome preceding the onset of multiple sclerosis - Mauritz, Matthias; Kliushnikova, Dariia; Otto, Ferdinand; Harrer, Andrea; Moser, Tobias; Radlberger, Richard Friedrich; Kleindienst, Waltraud; Trinka, Eugen; Wipfler, Peter (Frontiers in Immunology, 2025)
BackgroundThe reversible splenial lesion syndrome is frequently associated with systemic and central nervous system infections. Whether an infection associated with the occurrence of the reversible splenial lesion syndrome could play a role in the later development of multiple sclerosis is unknown.MethodsCase Report.ResultsA 27-year-old woman developed an infection-related reversible splenial lesion syndrome. Diagnostic findings did not establish a specific type of infection, but revealed evidence for a potential disposition towards autoimmunity. 32 months after the initial presentation, new clinical and radiological manifestations developed that led to a diagnosis of multiple sclerosis.ConclusionsIn susceptible individuals, infectious disease processes involving the central nervous system, such as described in this case, might be a factor in the pathogenesis of multiple sclerosis. More research on the prodromal stage of multiple sclerosis is needed to better understand the relationship between infections and autoimmunity.